2019
DOI: 10.3390/su11226426
|View full text |Cite
|
Sign up to set email alerts
|

Exploring On-Site Safety Knowledge Transfer in the Construction Industry

Abstract: A primary cause of occupational accidents is on-site workers not having proper or even adequate safety knowledge and awareness, leading to them failing to employ safety measures, equipment, or behavior to protect themselves. The complexity of construction projects and changes in organizational personnel complicate the safety knowledge transfer process. Therefore, to reduce occupational accidents in the construction industry, this study explored the on-site safety knowledge transfer process as well as its relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
2
21
0
1
Order By: Relevance
“…Failure to warn or secure members out of danger. This unsafe behaviour is highly reported in literature (Grytnes et al, 2020;Huang and Yang, 2019;Shamsuddin et al, 2015). On construction sites, accidents can easily occur if supervisors fail or ignore to warn other members who work on high risk tasks.…”
Section: Unsafe Behaviour In the Construction Industrysupporting
confidence: 58%
“…Failure to warn or secure members out of danger. This unsafe behaviour is highly reported in literature (Grytnes et al, 2020;Huang and Yang, 2019;Shamsuddin et al, 2015). On construction sites, accidents can easily occur if supervisors fail or ignore to warn other members who work on high risk tasks.…”
Section: Unsafe Behaviour In the Construction Industrysupporting
confidence: 58%
“…Harsini et al [ 52 ] clarified the effects of safety education interventions on workers’ unsafe behaviors through a mixed-method study (MMR). Huang and Yang [ 98 ] concluded that the transmission and popularization of safety knowledge in construction organizations is an effective method of creating a good safety atmosphere. Choi and Li [ 43 , 44 ] argued from the perspective of social identity that formulating work group norms are an effective way to improve worker safety behaviors.…”
Section: A State-of-the-art Review Of Related Literaturementioning
confidence: 99%
“…Bhasi and Vinodkumar [42] examined safety management practices and their influence on SB, results showed safety training is a key predictor of safety motivation, safety knowledge, safety participation, and safety compliance. The practice of transferring safety knowledge is of particular interest as it shown to deliver favorable SB outcomes [56]. Site interaction between laborers and supervisory staff all also plays an important role where effective communication has a significant influence on safety [23].…”
Section: Research Dimension Safety Participationmentioning
confidence: 99%